FPHP activities 2023: together we make it great / Fadhlina Mahat - Mahat, Fadhlina (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
The Faculty of Hotel and Tourism Management at UiTMCPP has blossomed into a dynamic hub of creativity and collaboration, weaving a rich tapestry of successful programs and activities that bring our entire community together, fostering a warm and lively atmosphere. From the Visiting Professor Program and the International Culinary Challenge, which feature a diverse array of global flavors, to the hands-on hotel management upskilling workshops, training sessions, conferences, and hospitality academic tours, as well as our active engagement in community services and collaborations, our faculty has truly become a kaleidoscope of enriching experiences, benefitting both students and lecturers. Through all the events, we have masterfully woven a beautiful tapestry of learning, unity, and success, making our faculty a thriving community where everyone's unique colors contribute to making it truly great.